Angola : Fourth Review Under the Stand-By Arrangement, Request for Waivers of Nonobservance of Performance Criteria, Request for Waivers of Applicability of Performance Criteria, and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2011)
Angola's economy was badly buffeted by the sharp drop in global oil prices. Policy discussions for the review focused on the 2011 budget, the handling of the arrears problem, monetary and exchange rate policies, and key elements of the authorities' administrative and policy reform agenda. Angolan banks have not been severely impaired by the financial instability of the past two years, and the sector maintains an adequate capital buffer. Four elements-public financial management, tax reform, improving the business environment, and transparency and safeguards issues-are discussed.